Factors affecting the use of home-based services and out-of-home respite care services: A survey of family caregivers for older persons with dementia in Northern Norway. (July 2020) - Moholt, Jill-Marit; Friborg, Oddgeir; Blix, Bodil H; Henriksen, Nils
Background: Family caregivers contribute substantially to the care for older home-dwelling people with dementia, although community healthcare services tend to be underutilized. In this study, we aimed to explore the use and predictors of use of home-based and out-of-home respite care services available to older home-dwelling persons with dementia, as reported by the family caregivers. Method: A cross-sectional survey was administered to family caregivers ( n = 430) in Northern Norway during April to November 2016. The use of healthcare services was categorized into two types according to principal component analysis: home-based services and out-of-home respite care services ( R 2 = 44.1%). Predictors of service use were examined with bivariate correlation, multiple linear regression, and Poisson regression analyses. Results: The use of home-based services among persons with dementia was significantly higher for persons with advanced age, persons living in urban areas, persons living in an assisted living facility, persons living alone, and persons able to manage being alone for a short period of time. Among the family caregiver variables, higher age, status as a daughter, son, or other family member, higher educational level, and full-time employment also predicted greater use of home-based services. Same ethnicity was associated with use of fewer home-based services. The use of out-of-home respite care services was significantly higher among male persons with dementia and among those living in urban areas. In addition, fewer out-of-home respite care services were used by male caregivers or daughters of the care recipient, while the use was higher when the caregivers experienced more caregiving demands or had provided care for longer periods of time. Conclusions: These results indicate areas that policymakers and healthcare providers should consider to identify families who underutilize healthcare services and to achieve a more equal and efficient allocation of services in accordance with families' needs.